Electromyographic validation of the double pulley equipment during movements of the lower limbs - Tassi, Nadir [UNESP]; Gonçalves, M. [UNESP] (My University, 2002)
The double pulley equipment was tested on ten male volunteers during contraction of the semitendinosus and biceps femoris (caput longum) muscles in the following movements of the lower limbs: 1) hip extension with extended knee and erect trunk, 2) hip extension with flexed knee and erect trunk, 3) hip extension with flexed knee and erect trunk, 3) hip extension with extended knee and inclined trunk, 5) hip abduction along the midline, 7) hip abduction with extension beyond the midline, 8) adduction with hip flexion beyond the midline, 8) adduction with hip flexion beyond the midline, and 9) adduction with hip extension beyond the midline. The myoelectric signals were taken up by Lec Tec surface electrodes connected to a 6-channel Lynx electromyographic signal amplifier coupled with a computer equipped with a model CAD 10/26 analogue digital conversion board and with a specific software for signal recording and analysis. The semitendinosus and biceps femoris muscles presented the highest potentials in movements 1; 2; 7, 8 and 9, whereas the potentials in the remaining movements were negligible. The pattern of activity of the semitendinosus and the biceps femoris was similar in exercises 1, 2, 3, 4 and 8. The potentials of the semitendinosus prevailed in movements 5, 6 and 7, and the strongest potentials observed in movement 9 were those of the biceps femoris.
Keywords: Biceps femoris; Double pulley; Electromyography; Semitendinosus; adult; amplifier; analog digital converter; computer program; computer system; controlled study; electrode; electromyography; equipment; exercise; hip; human; human experiment; joint function; kinesiology; knee function; leg; leg muscle; male; movement (physiology); muscle action potential; muscle contraction; myoelectricity; normal human; semitendinous muscle; signal processing; statistical analysis; validation process; Adolescent; Adult; Exercise; Humans; Lower Extremity; Male; Muscle Contraction; Muscle, Skeletal; Reference Values; Reproducibility of Results; Sports Equipment; Weight Lifting